Comparison of Instantaneous Reactive and Notch Filter Algorithms Seven Level Parallel Active Filter - Farouk Hadj Benali; Fouad Azzouz (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This work focused on the association of a seven level Neutral Point Clamped inverter and a parallel active filter. In order to test the efficiency of the 7 level parallel active filter, two reference current generating algorithms are used. The instantaneous reactive power algorithm and the notch filter algorithm. In this study, the instantaneous reactive power method and the notch filter method are presented. Than a section which gives a recall of the NPC multilevel inverter and PWM strategy. A comparison between the two reference current generating algorithms is made. The subjects of comparison are the total harmonic distortion (THD) and the fundamental value of the source current. The obtained simulation results have proved that the instantaneous reactive power technique is better than the notch filter technique. Simulations are carried out by PSIM program.